Analysis of the Relationship between HbA1c and Serum IGF-1 Levels in Patients with T2DM - Alya Rahmaditya Arfan; Liong Boy Kurniawan; Mansyur Arif; Husaini Umar; Nurahmi; Burhanuddin Bahar (Indonesian Association of Clinical Pathologist and Medical laboratory, 2023)
Type 2 Diabetes Mellitus (T2DM) is characterized by the reduced ability of insulin responses, leading to difficulty in processing blood sugar. It is caused by a combination of two main factors: damaged insulin secretion by pancreatic beta-cells and the inability of insulin-sensitive tissues to respond to insulin. Blood sugar monitoring in T2DM is done by measuring glycated hemoglobin or Hemoglobin A1c (HbA1c). Insulin Like Growth Factor-1 (IGF-1) is the primary mediator of growth hormone known to play a pivotal biological role in growth and metabolism. This study aims to analyze the relationship between HbA1c levels and serum IGF-1 levels in T2DM patients. The method used was observational analytic with a cross-sectional design. There were 60 T2DM patients involved as research subjects consisting of 26 males and 34 females. HbA1c examination was carried out using the Boronete Affinity Assay, while IGF-1 examination was performed using the Enzyme-Linked Immunosorbent Assay (ELISA) sandwich method. The statistical analysis results showed that the average value and standard deviation of serum IGF-1 levels in controlled T2DM was higher (5740.23±4320.60 pg/mL) than that of uncontrolled T2DM (4843.18±3375.63 pg/mL), showed no significant difference (p=0.462) and no correlation between HbA1c and serum IGF-1 levels in T2DM subjects (r=-0.005 p=0.972). It was concluded that there was no significant relationship between HbA1c levels and serum IGF-1 levels in patients with T2DM.